Une méthodologie d'analyse des effets de la globalisation sur les systèmes régionaux locaux - Silvana Lombardo (Unité Mixte de Recherche 8504 Géographie-cités, 1999)
The general aim of the study is to verify if and at what extent economic changes at global level influence territorial organisation, in terms of organisational models of the productive system and of firms location choices. The general lack of studies in this direction, due mainly to insufficient systematic information and to the specific features of many local territorial systems, led us to build a methodology aimed to increase the level of knowledge on these issues.In particular we worked on theoretical aspects, concerning both new models of territorial organisation, such as the network paradigm, and changes of the productive systems due to economic globalisation, such as the internationalisation; and empirical aspects, by analysing the productive systems of two Italian regions (Lazio and Abruzzo), which have been less analysed then other regions, but showed in recent years relevant changes, mainly concerning Small and Medium Firms and the formation of local productive systems able to ensure the adjustment to changing economic conditions.In order to analyse these two case studies, we chose to carry out a direct survey, based on a questionnaire direct to a sample of firms. The choice of data sources was not quite wide, because the new "privacy" law strongly limited the use of many data sources, so that we try to extract as many data as possible from available sources (data bases of Central Institute of Statistic and Italian Changes Office), and we construct some indicators in order :– to provide an adequate knowledge of the case studies, – to allow the simplification of the universe and to extract the sample, At the end we construct the questionnaire aimed to : – verify the general characteristics of firms and of their markets, and the level of external relations and the type of relations in which them are involved, – individuate and to evaluate the location factors' relevance.